Implementasi Projek Penguatan Profil Pelajar Pancasila Fase A Pada Tema Bhineka Tunggal Ika - Indra Kartika Sari; Ade Pifianti; Chairunissa Chairunissa (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2023)
The purpose of this study is to provide experience with project implementation activities to strengthen the profile of Pancasila students in phase A on the theme of Bhineka Tunggal Ika. This research used a qualitative descriptive approach and the data collection techniques used were the observation techniques by prioritizing direct data from the student information, as well as direct observations from the research location. The research location was at SD Avicenna Cinere grades 1 and 2, that was carried out from November to December 2022. The results obtained in this study in the dimensions of ‘Faith, Fear of God Almighty’, the Avicenna Elementary students understood that God created humans with all the differences and uniqueness in the ‘Dimension of Noble Morals’. It was found that the students understood to always be grateful for God’s blessings. The result in the ‘Global Diversity’ dimension showed that the students respect the physical, cultural, and background differences of the individuals around them. In the ‘Mutual Cooperation’ dimension, it was found that students could work together with their classmates both in group discussions or assignments. Lastly, in the ‘Creative’ dimension, students showed more creativity in completing their assignments, by providing creative ideas in group discussions.